Factors Impact on Internal Audit Effectiveness: The Case of Duhok University in Kurdistan-Iraq - Ahmed Yahya Abdullah; Aree Saeed Mustafa (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2020)
This study investigates the factors impact on internal audit effectiveness (IAE) in Kurdistan Iraq. Data were collected from 15 directors of Colleges and 15 internal audit managers at University of Duhok. The relationship between IAE and three principle factors has been examined using multiple regression analysis. Findings reflect that management support for IAE perceived effectiveness of internal audit from both directors of colleges and internal auditor’s perspective. Management support is related to occupy experienced and trained staff, providing sufficient resources. However, this study found insignificant relationship between independence of the internal audit and internal audit effectiveness